Photoshop elements 11 all-in-one for dummies / Barbara Obermeier, Ted Padova - Obermeier, Barbara
Bring out the best in your images with the latest version of Photoshop Elements Photoshop Elements is the top selling consumer photo editing software and Adobe continues to add innovative features that allow digital photo enthusiasts to do it all. This value-packed reference combines nine content-rich minibooks in one complete package. User-friendly and detailed, it covers the key features and tools that beginner and experienced users need to create high-quality images for print, e-mail, and the web using the latest release of Photoshop Elements: Photoshop Elements 11. Presented in full color